Educational Psychology - O'Donnell, A.; Dobozy, Eva; Bartlett, B.; Nagel, M.; Spooner-Lane, R.; Youssef-Shalala, A.; Reeve, J.; Smith, J. (John Wiley & Sons, 2016)
Teachers help students learn, develop and realise their potential. Educational psychology is the scientific study of how people learn and how teachers can foster learning. An understanding of these principles and how they can be applied to classroom situations is as crucial as it ever has been for the contemporary Australian school teacher, from early childhood through to secondary school. Building on the success of the first edition, Educational Psychology, Second Australian edition, draws together the pre-eminent academic voices in Australia’s educational psychology landscape. The culmination of the authors’ knowledge, hands-on experience and insight will help pre-service teachers develop a framework to implement teaching strategies that promote students’ learning, development and potential. Australian school students and learning environments are ever-changing. Many issues have an impact on the dynamics of the contemporary learning and teaching environment, including increasing student diversity, the pervasive impact of technology and the evolution of the Australian curriculum. The study of educational psychology can help teachers better understand their students and better understand the process of teaching. That is the primary purpose of this resource. Educational Psychology, Second Australian edition, also encourages pre-service teachers to become reflective practitioners who can frame classroom-based questions and use a ‘scientist–practitioner’ approach to answer those questions.It provides: a clear description of the theoretical principles in psychology that have relevance for education, along with an analysis of their current research support practical guidance about how to link theory and practice in the context of classrooms learning tools to help pre-service teachers develop skills they can build on throughout their teaching careers. Educational Psychology, Second Australian edition, prepares pre-service teachers for their profession by encouraging reflective practice and critical thinking in a jargon-free, accessible learning design. It helps inform the ‘prac’ teaching experience with extensive lesson plan analysis and hones developing skills with thought-provoking questions and activities.